DEVELOPMENT OF A TALENT SCOUTING ASSESSMENT POSTER MODEL FOR BEGINNER VOLLEYBALL ATHLETES - Restu Mullana; Anggri Dwi Nata; Rahmat Sanusi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to develop an effective and easy-to-use talent scouting assessment model poster to identify the talents and potential of beginner volleyball athletes. This study uses the Research and Development (R&D) method with the ADDIE development model. The population used was 31 students in total, then the researcher's sample with a small scale of 10 students and a large scale of 21 students, using a questionnaire instrument and using qualitative and quantitative data analysis. The results of the study indicate that the development of a poster model for talent scounting assessment according to design experts, material experts and user teachers is categorized as feasible. The development of talent scounting poster media for beginner soccer athletes is categorized as feasible.